Investigating the Risk and Protective Factors of Internet Addiction Among Adolescents through the Lens of Cognitive Behavioral Theory: A Cross-Sectional Study - Shaltout, Noura (AUC Knowledge Fountain, 2025)
—Introduction: The Internet has become a central part of modern life, enhancing education, providing means of global communication, and facilitating access to information and entertainment. However, an attendant risk of excessive Internet use is becoming unconsciously addicted to virtual online activities, especially when large tech companies design their products in a way that makes them addictive to users. These companies have the tools and knowledge that allow them to manipulate and transform the behavior of their target audience. Thus, this study aimed to investigate the potential risk and protective factors for Internet addiction among adolescents. Methodology: This cross-sectional study employed a self- administered assessment tool to investigate the determinants of Internet addiction among female and male students aged 17–21 years at the American University in Cairo (AUC). Using non-random convenience sampling, the study involved a quantitative approach that included responses from 171 participants. Building on the cognitive behavioral therapy (CBT) elements identified in the literature, this study focuses on maladaptive self-beliefs, behavioral patterns, and negative feelings as risk factors of compulsive Internet use. Other potential mediators, including self-efficacy, risk perception, and socio-demographic characteristics, were investigated as mediators of the association between the potential determinants of Internet addiction and the level of Internet addiction. Validated assessment tools from previous studies were used as references to identify the potential protective and risk factors. Correlation and multiple linear regression analysis were conducted to investigate the association between the proposed protective and risk factors and mediators of Internet addiction and the level of addiction using SPSS. Results: The analysis of participants showed that 30% were males, while 70% were females, with the majority falling in the age range of 18 to 20 years. A significant discrepancy in addiction rate was found between males and females (p=0.001). Multiple linear regression analysis revealed a significant positive association between mal-adaptive self-cognitions, risk perception, and the number of female siblings and Internet addiction in the sample, as evidenced by p- values of 0.005 and 0.01 and 0.017 respectively. Additionally, a notable negative association was found between self- efficacy and the level of Internet addiction, with a p-value of 0.001. Conclusion: Maladaptive self-beliefs, risk perception, and self-efficacy and the number of female siblings were found to be strong potential factors of Internet addiction. This, in turn, makes it imperative to develop effective strategies that address the potential determinants of Internet addiction among adolescents in Egypt. Keywords- Adolescents, Behavioral Addiction, Internet Addiction, Risk and Protective Factors